AN ECONOMIC ANALYSIS OF THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND THE ENVIRONMENT: IN IRAQ FOR THE PERIOD 2000-2017 - Shukr, Ali S.; Hameed, Basim H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The research aims to study the most important factors affecting carbon dioxide emissions Co2, through a model. Explanatory variables were used in the model, which are the average per capita gross domestic product (GDP), the square per capita gross domestic product (GDPSQ), per capita energy consumption (CONS), and the POP population for the period 2000-2017 via using double logarithmic formula which is more suitable for economic, statistical and econometric logic in this type of studies, the results of the research showed that all the explanatory variables were statistically significant at the level of 1% and that the model was significant as a whole according to the statistic F and the value of R2=0.99. Economically, we find that the parameter of the average per capita GDP was 0.46 and it came with a positive signal consistent with the methodology of the Environmental Curve Kuznets ECK, the parameter of per capita energy consumption was 0.04, and it came with a negative sign that contradicts the Kuznets methodology, the reason may belong to the conditions that affected the country after 2003. The research recommended to go to investing in renewable energy, because it is environmentally friendly, such as sun energy, and to reduce the size of the gas in the sectors emitting to it, such as the transport sector, factories, the extraction sector, and manufacturing industries, in order to preserve the integrity of the environment and the plant and animal wealth it contains ,to a better environment in Iraq.